Alamo all-stars - Hale, Nathan, 1976- (Hale, Nathan, 1976- Nathan Hale's hazardous tales., 2019)
Presents a graphic novel featuring the story of the Texans' last stand at the Alamo, when men like Jim Bowie, Stephen Austin, and Davy Crockett ended up barricaded in a fort against the entire Mexican army in a bid for Texas' independence.